Population hereditary structure of coral reef species Plectorhinchus flavomaculatus in South China Sea - Zhi Qiang; Zhoa T. Zang; Wehin P. I (Advances in Aquaculture and Fisheries Management, 2019)
The population genetic structure and the dispersal ability of PLECTORHINCHUS FLAVOMACULATUS from South China Sea were examined with a 464 bp segment of mtDNA control region. A total of 116 individuals were collected from 12 coral reefs in Xisha, Zhongsha and Nansha archipelagos and 22 haplotypes were obtained. Two lineages were detected, which might have diverged in different glacial refuge during Pleistocene low sea levels. Contrary to homogenization expectation, AMOVA and pairwise FST revealed significant genetic structure between Nansha and other two archipelagos (Xisha and Zhongsha). Pattern of isolation by distance was observed in this species, suggesting that mean dispersal distance of P. FLAVOMACULATUS is no more than 300 km. The different environment in glacial ages may cause the different pattern of population demography in lineages (stable model in lineage A and sudden expansion model in lineage B)